On the Speed of Transition in Central and Eastern Europe : Does On-the-Job Search Matter? - Brixiova, Zuzana (IMF Working Papers; Working Paper ;, 1997)
This paper examines how the on-the-job search of workers in the state sector who are seeking jobs in the private sector affects private sector employment, the unemployment level, and the unemployment duration in the transition economies of Central and Eastern Europe. The main finding is that on-the-job searching can account for the coexistence of a quickly growing private sector and a high unemployment level of long duration. The paper also addresses the issue of the optimal (output maximizing) rate of state sector closure and finds that the rate is slower when workers are simultaneously job hunting than when they are not.